Strategy, supply chain, and digital marketing for competitive advantage : A case of Shopee - William Ben Gunawan; Karina Boenardi; Yosephine Chrismayenita; Yudistiro Gilang Wicaksono; Tara Indri Edytia; Khoerul Lana; Zeus Priadika Priyono (Universitas Pendidikan Nasional, 2026)
This paper examines how Shopee, Southeast Asia’s leading e-commerce platform, integrates supply chain innovation, electronic marketing, and management to stay competitive in a rapidly evolving digital economy. Shopee’s success stems from its dynamic capabilities, especially data analytics and operational flexibility in responding to intense competition from Tokopedia, Lazada, and TikTok Shop. Using Porter’s Five Forces and PESTEL, this study highlights challenges such as low switching costs, strong buyer power, and rapid technological change, emphasizing the need for continuous strategic adaptation. Shopee’s electronic supply chain management and e-procurement systems improve efficiency and responsiveness, particularly in Indonesia’s complex geography. Vertical integration through Shopee Express, Shopee Hub, and tracking systems strengthens its value chain while supporting SMEs and enhancing customer satisfaction. Its mobile-centric marketing strategy, including live commerce, influencers, gamification, and personalized content, drives acquisition and retention. By leveraging consumer behavior favoring fast, interactive transactions, Shopee reduces friction in the purchasing process. Growing competition, especially TikTok’s ecosystem expansion, further intensifies the importance of trust and engagement. Overall, Shopee’s integrated approach to supply chain and digital marketing creates an innovation-driven model that strengthens its competitive position and supports digital inclusion across Southeast Asia. This model not only enhances operational resilience but also enables scalability in emerging markets. By aligning technology, logistics, and consumer engagement, Shopee maintains relevance amid shifting digital trends. Consequently, it remains a dominant platform shaping e-commerce development and empowering regional entrepreneurs to participate in the digital economy more effectively and sustainably over time, while fostering innovation, inclusivity, and long-term economic growth.